Troubling Love: Gender, Class, and Sideshadowing the "Happy Family" in Vietnam. (5th December 2017) - Shohet, Merav
Abstract: Though socially and politically different, Vietnam's Confucian, colonial, socialist, and marketizing regimes share a common master narrative of ideal women as the moral bedrock of their nation: virtuous, self‐sacrificing mothers. Drawing on ethnographic material collected in Đà Nẵng, this essay examines how women deploy discourses about ethical sentiments and national development to make sense of their experiences of love. I focus on women's moral struggles with and reasoning about sacrifice and care to complicate understandings of romantic love as linked to capitalist individualism and modernity. Instead, I show how women subtly critique, yet remain committed to, forms of love that reinforce—through state policy and common practice—hierarchical gender, intergenerational, and class relations. This is achieved through the telling and living of sideshadowing narratives, that is, subjunctive tales that invite contingency and contradiction. This nonteleological narrative practice reveals the precarious nature of ethical life and the ways love entangles political economy, moral sentiments, and moral reasoning. [morality and ethics, love, class and gender, narrative practice, Vietnam]